Detection of insect prey by wild common marmosets: The effect of color vision. Issue 3 (26th February 2019) - Abreu, Filipa; Souto, Antonio; Bonci, Daniela M. O.; Mantovani, Viviani; Pessoa, Daniel M. A.; Schiel, Nicola
Abstract: Most species of New World primates have an unusual color vision pattern that can affect an individual's ability to detect food. Whereas males can only be dichromatic, females can be either dichromatic or trichromatic. Trichromats are expected to have an advantage in detecting conspicuous food whereas dichromats should be better at locating cryptic resources. Here we aimed to understand how color vision phenotype influences insect foraging by five groups of common marmosets living in a semiarid environment. We recorded insect predation events, noting morphotype and color of the captured insect, and the substrate from which it was captured. Color modeling suggested that, for all values of chromatic contrast resulting from comparing the measured insect–substrate pairs, trichromats outperformed dichromats. Females showed an overall higher insect capture rate than males. Females also showed a higher capture rate of conspicuous insects but there was no sex difference for the capture of cryptic insects. When we compared only dichromatic individuals there was no difference between sexes. These findings suggest that differences found in capture rate related not only to sex but also to visual polymorphism and that the latter is a crucial factor determining insect capture rate in common marmosets. Nevertheless, these results should be interpreted with caution because of the small number (three) of dichromat females and the unknown phenotype of the remaining females. Our results support the balancing selection hypothesis, suggesting that the advantage of one phenotype over the other may depend on environmental circumstances. This hypothesis has recently been considered as the most plausible for the maintenance of visual polymorphism in New World primates. Abstract : Females of common marmosets showed an overall higher insect capture rate than males. Females also showed a higher capture rate of conspicuous insects but there was no sex difference for capture of cryptic insects. Dichromatic females and males, in turn, did not differ in insect capture rates. It appears that phenotype, but not sex, is the decisive factor that determines insect captures in these primates. It seems that trichromatic females have an advantage in insect foraging in semiarid environments. HIGHLIGHTS: Callithrix jacchus males and females capture similar rates of cryptic insects, whereas females capture more conspicuous insects. Among dichromats, insect captures do not differ. In semiarid environments, trichromats might have an advantage in insect foraging.